Apert syndrome: prenatal diagnosis challenge. Issue 12 (9th December 2019) - Vieira, Catarina; Teixeira, Neusa; Cadilhe, Alexandra; Reis, Isabel
Abstract : Apert syndrome is a rare genetic disorder that manifests as craniosynostosis, craniofacial and limb dysmorphic features. Mutations in fibroblast growth factor receptor 2 (FGFR2) gene account for almost all cases. Given the impact it can have throughout life, prenatal management becomes a challenge. A healthy 33-year-old woman, gravida 4, para 0, was referred to routine ultrasound at 22 weeks of gestation. Atypical cranial morphology with prominent forehead, ocular proptosis, hypertelorism and mitten hands were detected. Genetic investigation revealed an FGFR2 gene mutation (c.755C>G(p.Ser252Trp)), confirming the diagnosis. Magnetic resonance showed brachycephaly, turricephaly and cortical malformation. Following counselling, parents requested medical termination of pregnancy. Macroscopic features were consistent with ultrasound findings. This case emphasises the importance of early diagnosis to provide the best family counselling and prenatal management. A multidisciplinary team, consisting of an obstetrician with ultrasonography experience, a medical geneticist and a fetal pathologist, should conduct these cases.